ANALISIS KINERJA KEUANGAN SEBELUM DAN SESUDAH AKUISISI PADA PERUSAHAAN SEKTOR NON-KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Samuel Karuniawan Wiryandi (2022)
This research aims to determine differences in financial performance pre and post the acquisition. The population of this research were non-financial sector companies listed on the IDX and made acquisitions in 2016-2018 with observations 3 years pre the acquisition and 3 years post the acquisition, there were 25 companies which were also used as research samples. The research variables are the ability to pay debts (current ratio), the ability to manage debt (debt to equity ratio), the ability to manage assets (total asset turnover) and the ability to generate profits (return on equity). The data analysis technique used was the Shapiro-Wilk method with the Paired sample t-test and the Wilcoxon signed-rank test. The results showed that there was a difference in performance on the ability to manage assets variable. However, there is no difference in performance on the variables of ability to pay debts, ability to manage debt, and ability to generate profits.